Towards p-11B medium configurations with high Pfus/PBrems ratios - Daponta, C.; Moustaizis, S.; Eliezer, S.; Henis, Z.; Lalousis, P.; Nissim, N.; Schweitzer, Y. (Frontiers in Physics, 2024)
The aneutronic p-11 B nuclear fusion is promising for clean energy production, as it produces three (3) alpha particles with 8.7 MeV total energy. However, the main difficulty for p-11 B fusion ignition (Q = P fus / P Brems ≥ 1) concerns the nuclear cross-section and thus, reactivity efficiency, at higher than 200 keV medium temperatures. For the overcome of this difficulty, the present work emphasizes on the numerical investigation of medium schemes (configurations) with enhanced reactivity. The configurations refers to the addition of energetic protons in a low-density 11 Boron or proton -11 Boron medium (n = 10 20 m -3 ), with (n p / n B ) > 1 for Bremsstrahlung losses optimization and initial temperature in the range of 1 keV ≤ T in ≤ 400 keV. A selfconsistent multi-fluid global particle and energy balance code, including collisions between all medium species (p, 11 B, e, α), is used for the description of the temporal evolution of all fusion medium physical parameters and the evaluation of the optimum initial conditions for the obtainment of Q ≥ 1. The numerical simulation results show that, the coupling between the 200 keV < E p,0 ≤ 750 keV energetic protons and the 1 keV ≤ T in ≤ 400 keV initial fusion medium, leads to ignition: 1 ≤ Q < 1.4, below T in = 100 keV. In all the presented initial medium temperature cases and especially, the lower (<) than 100 keV, the ignition condition (P fus / P Brems ) > 1 arises, as a consequence of the chain reactions and the related avalanche alpha heating effect.